Edukasi Mitigasi Bencana Banjir Bandang Di Desa Pulu Kecamatan Dolo Selatan Kabupaten Sigi - Mulyati, Sri; Abdullah, Abdullah; Rusli, Rusli; Musa, Dahlan Th.; Kurniawan, Mauludin; Kasim, Sandra; Asrafil, Asrafil (-, 2025)
Disaster education activities on flash floods were carried out in Pulu Village, Dolo District, Sigi Regency as an effort to increase community knowledge and preparedness against the threat of flash floods. The method used was a participatory approach involving the direct participation of the Pulu Village community, the Village Government, community leaders, and Disaster Response Youth. The stages of this community service activity included location observation, preparation, and implementation. The implementation stage was conducted through a socialization or outreach scheme in the form of a lecture. The purpose of the education was to introduce signs of flash flood hazards, risk knowledge, and emergency response planning. The educational activity received positive responses from the community, who actively engaged during the presentation, as well as appreciation from the village government. The presentation of materials accompanied by a simple simulation further enhanced the community’s understanding of self-rescue actions during a flash flood. The results of this activity indicate that interactive disaster mitigation education can effectively build community awareness and preparedness in facing flash flood threats.